Fish farming systems for Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Asian know-how is being used to develop fish farming systems for Africa. (As reported in Spore 29 page 10). Researchers from the International Centre for Living Aquatic Resources Management (ICLARM) working with the University of Malawi and the...